2013
DOI: 10.3109/1061186x.2013.839688
|View full text |Cite
|
Sign up to set email alerts
|

An improved radiolabelled RNA aptamer molecule for HER2 imaging in cancers

Abstract: Human epidermal growth factor receptor 2 (HER2) expression has been shown to be increased in several types of human tumours. In this study, for the imaging of HER2-related tumours, a modified RNA aptamer with HER2-specific targeting was labelled with (99m)Tc, by using hydrazino nicotinamide (HYNIC) as the chelator in the presence of tricine or ethylenediamine-N,N'-diacetic acid (EDDA) as the co-ligand. Stability testing of the radiolabelled aptamers in the serum was performed through SDS-PAGE. The aptamer-radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Although preclinical studies were successful [45,46,47,48,49], only a few clinical studies have been reported and results were disappointing since radiotracer uptake in tumors was absent or low [50,51]. Also, radiolabeled HER2-targeting RNA aptamers were synthesized for targeting HER2-positive BC lesions [52]. These studies are still in a preclinical setting and their advantage to HER2-targeting antibodies, affibodies, and nanobodies remains to be established.…”
Section: Human Epidermal Growth Factor Receptor 2 (Her2)-targeted mentioning
confidence: 99%
“…Although preclinical studies were successful [45,46,47,48,49], only a few clinical studies have been reported and results were disappointing since radiotracer uptake in tumors was absent or low [50,51]. Also, radiolabeled HER2-targeting RNA aptamers were synthesized for targeting HER2-positive BC lesions [52]. These studies are still in a preclinical setting and their advantage to HER2-targeting antibodies, affibodies, and nanobodies remains to be established.…”
Section: Human Epidermal Growth Factor Receptor 2 (Her2)-targeted mentioning
confidence: 99%
“…An increasing accumulation of radiolabelled aptamer in time (up to 5 h p.i.) has been often observed with other aptamers [19,20,[47][48][49].…”
Section: Tumour Uptakementioning
confidence: 99%
“…Several aptamers targeting HER2 have been reported [11][12][13][14][15][16][17][18]. So far, only one of these aptamers has been radiolabelled (with 99mTc) and its biodistribution was evaluated ex vivo [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A modified RNA aptamer with HER2-specific targeting was labeled with 99m Tc and allowed SPECT imaging of HER2 expression (26,27). Another group used 64 Cu-WT4340 for PET imaging of HER2 messenger RNA and also demonstrated its successful use for evaluating the therapeutic efficacy of doxorubicin therapy in immunocompromised mice carrying human HER2-positive BC xenografts (28).…”
Section: Preclinical Settingmentioning
confidence: 99%